Методи моделювання резонансно-тунельного діоду - Яцун, К. С. (ХНУРЕ, 2021)
The work is devoted to methods for modeling the frequency characteristics of a GaAs composite semiconductor based on a resonant tunneling diode, presented in mathematical form with the aim of further constructing a theoretically calculated current-voltage characteristic of a diode in accordance with the experimental characteristic. In particular, the method of transfer matrices, which belongs to conditionally analytical methods for calculating electronic transparency, and the method of Green's function, which is a numerical method for calculating transparency, are considered.
Keywords: моделювання резонансно-тунельного діоду